A Survey on Electric / Hybrid Vehicles - Ribeiro, Bernardo (2010)
Since the late 19th century until recently several electric vehicles have been designed, manufactured and used throughout the world. Some were just prototypes, others were concept cars, others were just special purpose vehicles and lately, a considerable number of general purpose cars has been produced and commercialized. Since the mid nineties the transportation sector emissions are being increasingly regulated and the dependency on oil and its price fluctuations originated an increasing interest on electric vehicles (EV). A wide research was made on existing electric/hybrid vehicle models. Some of these vehicles were just in the design phase, but most reached the prototype or full market production. They were divided into several types, such as NEVs, prototypes, concept cars, and full homologated production cars. For each type of vehicle model a technical historic analysis was made. Data related to the vehicle configuration as well as the embedded systems were collected and compared. Based on these data future prospect of evolution was subsequently made. The main focus was put on city vehicles and long range vehicles. For city vehicles the market approach normally consists in the use of full electric configuration while for the latter, the hybrid configuration is commonly used. The electrical systems and combustion engines found in these vehicles are compared in order to forecast the evolution trend in terms of specifications and performance of the whole vehicle and of each system.